Deimination level and peptidyl arginine deiminase 2 expression are elevated in astrocytes with increased incubation temperature - Enriquez Algeciras, Mabel (2015)
Astrocytes respond to environmental cues, including changes in temperatures. Increased deimination, observed in many progressive neurological diseases, is thought to be contributed by astrocytes. We determined the level of deimination and expression of peptidyl arginine deiminase 2 (PAD2) in isolated primary astrocytes in response to changes on either side (31°C and 41°C) of the optimal temperature (37°C). We investigated changes in the astrocytes by using a number of established markers and accounted for cell death with the CellTiter‐Blue assay. We found increased expression of glial fibrillary acidic protein, ALDH1L1, and J1‐31, resulting from increased incubation temperature and increased expression of TSP1, S100β, and AQP4, resulting from decreased incubation temperature vs. optimal temperature, suggesting activation of different biochemical pathways in astrocytes associated with different incubation temperatures. Mass spectrometric analyses support such trends. The PAD2 level was increased only as a result of increased incubation temperature with a commensurate increased level of deimination. Actin cytoskeleton and iso[4]LGE, a lipid peroxidase modification, also showed an increase with higher incubation temperature. Altogether, these results suggest that temperature, as an environmental cue, activates astrocytes in a different manner on either side of the optimal temperature and that increase in deimination is associated only with the higher temperature side of the spectrum.